NETWORKING THE CULTURAL HERITAGE OF THE ESTONIAN DIASPORA: ATTEMPTS AND EXPERIENCES - NOORHANI, PIRET (Knygotyra, 2015)
Estonian National Museum Veski 32, 51014 Tartu, Estonia E-mail: piretnoorhani@gmail.com After leaving the homeland at times of World War II Estonians started collecting their cultural heritage. Special archives and libraries were organized in Australia, Sweden, USA and Canada, some of them, still active. Since the end of 1980s memory institutions in Estonia also have been collecting the cultural heritage of expatriates. Large collections have been formed and a lot of research has been done by them. Numerous contacts and cooperation projects have been developed between the archivists, librarians and museologist in Estonia and world wide Estonian communities. The article gives an account of our experience and discusses the further possibilities for networking the cultural heritage of both the Estonian and the Baltic Diasporas